DEBATES ON FAMILY ISSUES - Holtzman, Mellisa (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Working in groups of four, two members of the group will take a "pro" position and two will take a "con" position with respect to the group’s assigned topic. Groups will be expected to research their topic to find as much supporting evidence as possible. Begin by consulting assigned class readings that are relevant to the topic, and then conduct additional research and utilize materials not provided in class texts in order to be fully prepared for the debate.